Bone Lid Technique Using a Piezoelectric Device for the Treatment of a Mandibular Bony Lesion - Ronald Younes; Ibrahim Nasseh; Pierre Lahoud; Elie Wassef; Maroun Dagher (Case Reports in Dentistry)
Different techniques for the enucleation of jaw cyst lesion in the oral and maxillofacial regions have been proposed, including the bone lid technique. The purpose of this case report is to describe the case of a cystic lesion, approached with the bone lid technique performed using a piezoelectric device, with an 8-month clinical and radiographic follow-up. A 14-year-old male patient was treated for a suspicious lesion detected on a panoramic radiograph. The concerned area was surgically accessed, and a radiographically predetermined bony window was drawn, and the beveled bony lid was removed. The underlying lesion was enucleated and sent for pathology as a routine procedure, and the removed bony lid was repositioned in situ and secured with a collagen tape. Healing was uneventful with limited swelling and reduced pain. A complete radiographic bone healing at the previously diseased site was confirmed with an 8-month cone beam computed tomography (CBCT) scan with no buccal bone resorption nor ridge collapse. The bone lid technique with a piezoelectric device was noninvasive and atraumatic in this case. Further studies are needed and could lead to the adaptation of this approach as a possible standard of care.